Sediment cytology in diagnostic evaluation of oral neoplasms - Vishakha V Chaudhari; Rishikesh Dandekar; Aarti M Mahajan; Nilima Prakash (Wolters Kluwer Medknow Publications, 2014)
Aim: To evaluate the role of sediment cytology of biopsy specimen fixatives in early diagnosis of oral neoplasms. Materials and Methods: Cytological smears were prepared by centrifuging the fixatives in which the biopsy specimens were received. The smears were analyzed and the cytological results were compared with histological diagnosis. Results: Of 20 lesions studied by sediment cytology, 8 were labeled as benign, 9 as malignant and 3 cases as inconclusive. Final histopathological diagnosis labeled 12 lesions as malignant and 8 lesions as benign. Comparing the cytological diagnosis with histological sections, 17 out of 20 cases were concordant. The overall diagnostic accuracy of 85% was achieved. Conclusion: Biopsy sediment cytology is a good complimentary method to histopathology in the study of oral biopsy material.